Interaction between cisplatin and radiation in the treatment of ovarian cancer cells - LeBlanc, Julie-Maude (University of Ottawa (Canada), 2003)
The A2780s is a cisplatin and radiation-sensitive human ovarian carcinoma cell line from which the more resistant variant, A2780cp, was derived. In vitro experiments on the radiosensitivity of these cells with different treatments may be representative of the in vivo radiosensitivity, and maybe of use to patients receiving radiotherapy. Therefore, many studies have been directed at evaluation of the inhibition of DNA repair in order to improve radiotherapy. Previous studies showed that drugs and hyperthermia are repair inhibitors increasing the effectiveness of radiation. Cisplatin can also radiosensitize the A2780s and A2780cp and inhibit the sublethal damage repair (SLDR) (Raaphorst et al., 1995a). In this study we found no radiosensitization in the A2780s and A2780cp cells when cisplatin is added immediately before or after radiation. When cisplatin was added 24 hours prior to radiation, no increase in cellular resistance (adaptive response) to radiation treatment was observed. On the other hand cisplatin induced resistance when added during a pulse dose rate (PDR of 1 Gy/h) radiation treatment.
Keywords: Health Sciences, Radiology.; Biophysics, Medical.; Health Sciences, Oncology.